The Role of Endothelial Progenitors in the Repair of Vascular Damage in Systemic Sclerosis - Del Papa, Nicoletta; Pignataro, Francesca (Frontiers in Immunology, 2018)
Abstract Systemic Sclerosis (SSc) is a connective tissue disease characterized by a complex pathological process where the main scenario is represented by progressive loss of micro-vascular bed, with the consequent progressive fibrotic changes in involved organ and tissues. Although most aspects of vascular injury in scleroderma are poorly understood, recent data suggest that the scleroderma impairment of neovascularization could be related to both angiogenesis and vasculogenesis failure. Particularly, compensatory angiogenesis does not occur normally in spite of an important increase in many angiogenic factors either in SSc skin and serum. Besides insufficient angiogenesis, the contribution of defective vasculogenesis to SSc vasculopathy has been extensively studied. Over the last decades, our understanding of the processes responsible for the formation of new vessels after tissue ischemia has increased. In the past, adult neovascularization was thought to depend mainly on angiogenesis (a process by which new vessels are formed by the proliferation and migration of mature endothelial cells). More recently, increased evidence suggests that stem cells are mobilized from the bone marrow into the peripheral blood, differentiate in circulating endothelial progenitors (EPCs), and home to site of ischemia to contribute to de novo vessel formation. Significant advances have been made in understanding the biology of EPCs, and molecular mechanisms regulating EPC function. Autologous EPCs now are becoming a novel treatment option for therapeutic vascularization and vascular repair, mainly in ischemic diseases. However, different diseases such as cardiovascular diseases, diabetes and peripheral artery ischemia are related to EPC dysfunction. Several studies have shown that EPCs can be detected in the peripheral blood of patients with SSc and are impaired in their function. Based on an online literature search (PubMed, EMBASE, and Web of Science, last updated December 2017) using keywords related to “endothelial progenitor cells” and “Systemic Sclerosis”, “scleroderma vasculopathy”, “angiogenesis”, “vasculogenesis”, this review gives an overview on the large body of data of current research in this issue, including controversies over the identity and functions of EPCs, their meaning as biomarker of SSc microangiopathy and their clinical potency.